Le proteine coinvolte nella modulazione del dolore: TRPV1, NGF, OPR e GABA B - The proteins involved in pain modulation: TRPV1, NGF, OPR and GABA B - Francesco Amato; Erminia Gilda Morrone (Publiediting, 2016)
TRPV1 is well known as a sensor ion channel that transduces a potentially harmful environment into electrical depolarization of the peripheral primary afferents terminals. Recent studies have shown a clear structural and functional crosstalk between the TRPV1 and ANO1, which intervenes in the analgesic action of capsaicin. Through a series of intracellular signaling pathways, NGF increases the number of the TRPV1 on the sensory nerve fibers (by increasing the p38 and mRNA) and sensitizes the same receptor channel. The activation of the MORs causes a decreased PKA's activity (Protein Kinase A), responsible for phosphorylation of residues S 502, S 800 of TRPV1 (Transient Receptor Potential channels) which transduce noxious impulses. In addition, recent biochemical studies have shown that the TRPV1 and GABA B1 are closely linked in DRG neurons. The presence of GABA B1 with channels TRPV1 can change the currents induced by capsaicin. TRPV1, NGF, OPRs, and GABA B are new therapeutic targets involved in pain.